Energy conversion at dipolarization fronts. Issue 3 (13th February 2017) - Khotyaintsev, Yu. V.; Divin, A.; Vaivads, A.; André, M.; Markidis, S.
Abstract: We use multispacecraft observations by Cluster in the Earth's magnetotail and 3‐D particle‐in‐cell simulations to investigate conversion of electromagnetic energy at the front of a fast plasma jet. We find that the major energy conversion is happening in the Earth (laboratory) frame, where the electromagnetic energy is being transferred from the electromagnetic field to particles. This process operates in a region with size of the order several ion inertial lengths across the jet front, and the primary contribution toE ·j is coming from the motional electric field and the ion current. In the frame of the front we find fluctuating energy conversion with localized loads and generators at sub‐ion scales which are primarily related to the lower hybrid drift instability excited at the front; however, these provide relatively small net energy conversion. Key Points: Conversion of electromagnetic energy at plasma jet fronts is investigated using spacecraft observations and 3‐D PIC simulations The largest EC is found in the laboratory (Earth) frame, where most of the EM energy is being transferred to ions accelerated by the front No significant EC in the frame moving with the front